2001
DOI: 10.1016/s1097-2765(01)00217-9
|View full text |Cite
|
Sign up to set email alerts
|

The Large Subunit of Replication Factor C Promotes Cell Survival after DNA Damage in an LxCxE Motif– and Rb-Dependent Manner

Abstract: Retinoblastoma (Rb) protein promotes cell survival after DNA damage. We show here that the LxCxE binding site in Rb mediates both cell survival and cell-cycle arrest after DNA damage. Replication factor C (RF-C) complex plays an important role in DNA replication. We describe a novel function of the large subunit of RF-C in promoting cell survival after DNA damage. RF-Cp145 contains an LxCxE motif, and mutation of this motif abolishes the protective effect of RF-Cp145. The inability of wild-type RF-Cp145 to pro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

4
57
0

Year Published

2004
2004
2020
2020

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 49 publications
(61 citation statements)
references
References 42 publications
4
57
0
Order By: Relevance
“…Frag1 has a conserved AAA family motif, a hallmark of the ATPase family associated with various cellular activities, including chaperone-like functions that assist in the assembly, operation, or disassembly of protein complexes. Comparison of the mouse and human Frag1 amino acid sequences indicated that they conserve putative Atr-phosphorylation sites (mouse Frag1 at Ser-1150 and Ser-1168 and human Frag1 at Ser-1169 and Ser-1187) (18,19), and a putative Rb binding site with a Leu-x-Cys-x-Glu (LxCxE) motif (amino acids 1409-1413 of mouse and 1428-1432 of human) (20).…”
Section: Resultsmentioning
confidence: 99%
“…Frag1 has a conserved AAA family motif, a hallmark of the ATPase family associated with various cellular activities, including chaperone-like functions that assist in the assembly, operation, or disassembly of protein complexes. Comparison of the mouse and human Frag1 amino acid sequences indicated that they conserve putative Atr-phosphorylation sites (mouse Frag1 at Ser-1150 and Ser-1168 and human Frag1 at Ser-1169 and Ser-1187) (18,19), and a putative Rb binding site with a Leu-x-Cys-x-Glu (LxCxE) motif (amino acids 1409-1413 of mouse and 1428-1432 of human) (20).…”
Section: Resultsmentioning
confidence: 99%
“…Accordingly, mutation(s) of these contact residues suppressed the ability of Rb to bind LXCXE-containing viral proteins. These Rb mutants retain the ability to bind E2F, repress E2F-1-dependent transcription, and inhibit growth comparable with wild type Rb (26,27) but fail to protect cells from apoptosis (14).…”
mentioning
confidence: 97%
“…12). In addition, Rb inhibits cell death induced by DNA-damaging agents (13,14) or E2F-1 (15). The demonstration that Rb null mice die at 13-15 days of gestation accompanied by increased cell death in multiple organs (16 -18) suggests that Rb plays a critical role in regulating apoptosis.…”
mentioning
confidence: 99%
See 2 more Smart Citations